Biotrade of Colombian Cosmetic Ingredients as an Opportunity to Harnessing the Free Trade Agreement with South Korea (2022)
With 16 trade agreements signed and after 3 decades of the economic opening, Colombia faces important challenges to achieve the expected results with economic integration. Diversification of the export portfolio, participation in global value chains and the revitalization of the economy continue to be goals in development. Understanding that new production and consumption trends are decisive in the effective access to international markets, this article proposes to inquire about the opportunities of Biotrade to serve as a mechanism to facilitate the insertion of national offer in the beauty and skin care industry in South Korea. In five sections, this article refers to the current state of the trade balance with South Korea, Colombia’s comparative advantages in terms of natural ingredients derived from biodiversity, regulatory developments in Biotrade, the characteristics of voluntary certifications as competitiveness tools, and an approach to the conditions of the national offer. The conclusions highlight the importance of sustainability for the destination market, the remaining gaps in national public policy, and the need to deploy comprehensive strategies to facilitate the harnessing of trade agreements.